Tantangan Keuangan Islam dI Era Globalisasi - Fahrurrozi Fahrurrozi; Cici Wilantini; Novita Tri Buana Dewi (Perisai : Islamic Banking and Finance Journal, 2019)
Globalization is a worid development that removes boundaries that make communication or interaction between countries difficult for one another. With globalization everything will be easier to do. From the economic aspect, globalization is able to make an investor easily invest their funds in oither countries. For this convenience, it triggers fraud that might be carried out by people who are not responsible especially in Islamic finance. Where islamic finance is a financial cycle that cannot be interfered with by unclean funds or unclear origins. So globalization is also a new challenge for islamic finance itself.